Предмет: Алгебра,
автор: ломка228
(x-4)×(x-2)-(x-1)×(x-3) при x=одна целая три седьмых плиз помагите можно просто ответ а желательно расписать буду рад если поможите
Ответы
Автор ответа:
0
(x-4)*(x-2)-(x-1)*(x-3)=x^2-2x-4x+8-(x^2-3x-x+3)=x^2-6x+8-x^2+3x+x-3=
=-2x+5
x=1 3/7
-2*1 3/7 + 5 = -2*9/7 + 5 = -18/7 + 35/7 = 35/7 - 18/7 = 17/7=2 3/7
=-2x+5
x=1 3/7
-2*1 3/7 + 5 = -2*9/7 + 5 = -18/7 + 35/7 = 35/7 - 18/7 = 17/7=2 3/7
Автор ответа:
0
спсибо
Похожие вопросы
Предмет: Математика,
автор: unysovsultan
Предмет: Математика,
автор: rtorozanov
Предмет: Математика,
автор: SaxarokUwU
Предмет: Математика,
автор: vikaanya7303
Предмет: Математика,
автор: KarinkaSologub